The Indonesian government responds to protecting the natuna area through the utilization of national security - Iswardhana, Muhammad Ridha (The International Journal of Politics and Sociology Research, 2024)
The primary aim of this research is to enhance surveillance of the sea area in Natuna using the principles of national security. This policy entails the Indonesian government's strategic utilization to validate Jakarta’s national interests in Natuna vis-à-vis China. Concurrently, the national security strategy underscores a range of endeavors to protect Indonesia's sovereignty beyond military defense. This article to demonstrate that Indonesia possesses a robust bargaining position in safeguarding the Natuna region. This research adopts a qualitative approach centered on the analysis of specific case studies. The descriptive-explanatory methodology elucidates Indonesia's policies in securing its maritime interests in Natuna. Indonesia's significance as a nation and its unwavering commitment to preserving its territorial integrity. This study not only for reference, but also to foster national pride, and offer valuable perspectives for the nation.